1994
DOI: 10.1111/j.1745-4530.1994.tb00337.x
|View full text |Cite
|
Sign up to set email alerts
|

CONVECTIVE HEAT TRANSFER COEFFICIENT FOR CUBIC PARTICLES IN CONTINUOUS TUBE FLOW USING the MOVING THERMOCOUPLE METHOD1

Abstract: The convective heat transfer coefficient, hfp, between fluid and cubic particles was investigated with respect to flow rate, viscosity, and particle to tube dimension ratio using a moving thermocouple method. This study was conducted for a single particle. the determined values of hfp ranged from 199 W/m2C and 749 W/m2C. Results indicate that an increase in viscosity or dimension ratio decreased hfp values. In contrast, an increase in flow rate increased values of hfp. the effect of particle to tube dimension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…For particle to tube size ratio, h, values increased when the particle size decreased (p <0.05). The above observation is similar to the result obtained using moving thermocouple methods (Zitoun and Sastry 1994), but there is an apparent inconsistency with the results obtained by Sastry et al (1990). The principal reason for the difference is the flow regime: laminar in the present instance; fully developed turbulence in the earlier study.…”
Section: Liquid Crystal Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…For particle to tube size ratio, h, values increased when the particle size decreased (p <0.05). The above observation is similar to the result obtained using moving thermocouple methods (Zitoun and Sastry 1994), but there is an apparent inconsistency with the results obtained by Sastry et al (1990). The principal reason for the difference is the flow regime: laminar in the present instance; fully developed turbulence in the earlier study.…”
Section: Liquid Crystal Methodssupporting
confidence: 83%
“…More recent work from this laboratory (Balasubramaniam and Sastry 1994) has found that under laminar flow conditions, the effect of particle-to-pipe dimension ratio was not clear cut; this was attributed to variation in particle trajectories (which were not controlled). Zitoun and Sastry (1994) determined convective heat transfer coefficients for cubic particles in non-Newtonian carrier fluids in laminar flow using the moving thermocouple approach of Sastry et al (1990). Results indicated increasing heat transfer coefficients with increasing flow rate, decreasing viscosity and decreasing particle-to-tube dimension ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…That coefficient and data on residence time distribution are necessary to design different processes, such as those in which particles are moving through a heat exchanger and holding tubes sections (as is the case of aseptic processing systems). Different correlations to predict fluid-to-particle heat transfer coefficients (h fp ) for processing of particle foods flowing in tubes have been developed recently to solve this kind of problems (Sastry & Zuritz, 1987;Chandarana, Gavin, & Wheaton, 1990;Zuritz, McCoy, & Sastry, 1990;Mwangi, Datta, & Rizvi, 1992;Balasubramaniam, 1993;Zitoun & Sastry, 1994a, 1994bAstrom & Bark, 1994;Bhamidipati & Singh, 1995;Awuah & Ramaswamy, 1996;Chakrabandhu & Singh, 1998). Zareifard (2000, 2003), and Zareifard and Ramaswamy (2001) developed correlations for experimental data obtained from two techniques allowing particle motion during the heating process: a calorimetric method (CM) in which the particle was free to move and rotate along the length of holding tube, and a particle oscillatory motion method (POMM) in which particle was allowed a controlled movement in an oscillatory fashion.…”
Section: Dimensional Analysis Applied To Convection Heat Transfer In mentioning
confidence: 99%
“…Heat penetration measurements for a food particle traveling through an aseptic processing system are difficult and not practical at the present time without restricting the free movement of food particles (Sastry 1986; Lee and Singh 1990; Heldman 1992; Maesmans and others 1994). Due to challenges encountered in measuring the temperature of moving particles in aseptic processing systems, several alternatives have been considered, such as biological validation techniques (Cacase and others 1994), moving thermocouple methods (Sastry 1992; Zitoun and Sastry 1994a), liquid crystal technique (Zitoun and Sastry 1994b), time temperature integrators (Guiavarc'h and others 2002), melting point indicators (Mwangi and others 1993), and relative velocity methods (Balasubramaniam and Sastry 1994).…”
Section: Introductionmentioning
confidence: 99%